(untitled) (Nordic Journal of Practical Theology, 2026)
The article examines the significance of confessional culture for conceptions of vocation, gender roles, and organizational forms within the Deaconess Institution and the Deacon Institution during the period circa 1850–1910. Confessional culture is placed within an intellectual-historical perspective and is linked to the changing role of the Church in the transition from an agrarian society to modernity. The study shows that the traditional Lutheran understanding of the household’s responsibility for one’s neighbor, as part of the earthly calling, was redefined within diaconal work into an understanding in which the work of deacons and deaconesses is seen as a necessary expression of evangelical love in society and its institutions. Within diakonia, an ideological shift thus occurs from law to gospel. The fact that women were given a professional position outside the home, and that men performed care work, was justified through this understanding of Christian social responsibility. Both the deaconess and deacon institutions were shaped by the notion of the institution as a household. This understanding entailed a modification of the Lutheran concept of the household, while at the same time reflecting a structural continuity with it. The institutions were pioneering actors in the emergence of early welfare professions—an initiative that should be understood against the background of its ideological context and the early processes of modernization.